Chapter 1 Dynamics of Bordering in the Post-Soviet Space over the Last 30 years - von Löwis, Sabine (Taylor & Francis, 2023)
The disintegration of the Soviet Union changed the status of the borders of its republics: internal administrative borders became international ones that were redefined by treaties between the successor republics, and the former external borders of the Union were similarly redefined. This article shows how these negotiations and further bordering developed differently in the regions of the Baltic States, the western post-Soviet states, the Caucasus, and Central Asia. Various influencing factors played out differently: previous social, cultural, and political orders; nation-building efforts; economic and structural linkages; and competing regional and international political projects. Peace has prevailed around most of the borders, and the population has created ways to maintain social relations. However, starting with the conflicts in the Caucasus in the early 1990s, unresolved conflicts over borders of the successor republics have increased.